2002
DOI: 10.1038/sj.bmt.1703368
|View full text |Cite
|
Sign up to set email alerts
|

Portal vein thrombosis after hematopoietic cell transplantation: frequency, treatment and outcome

Abstract: Summary:Patients who develop veno-occlusive disease (VOD) of the liver may have low plasma levels of the natural anticoagulants protein C and antithrombin III, but large vessel thromboses are not commonly reported in these patients. We reviewed the records of 1847 consecutive patients for evidence of portal vein thrombosis. Eight patients (0.4%) developed portal vein thrombosis (PVT) at a median of day +28 (range 3-58). All patients had clinical evidence of VOD with ascites, a median total serum bilirubin 11.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Serious adverse events due to procedural complications in combination with underlying disease conditions (e.g. veno-oclusive disease) have been reported during clinical experience with HSC transplantation [99,100]. …”
Section: Risk Factorsmentioning
confidence: 99%
“…Serious adverse events due to procedural complications in combination with underlying disease conditions (e.g. veno-oclusive disease) have been reported during clinical experience with HSC transplantation [99,100]. …”
Section: Risk Factorsmentioning
confidence: 99%
“…Therefore, high dose of cells may be needed for therapy, increasing the risk of unwanted effects. Finally, concentrated cells may form aggregates and lead to pulmonary emboli or infarctions following administration , especially when intravenously infused, as demonstrated in hematopoietic stem cell (HSC) transplants . A recent study showed no serious side effects, systemic infection or cancer was associated with SVF cell therapy in a total of 1114 patients who received SVF for the treatment of osteoarthritis , indicating a safe profile of SVF, at least following intra‐articular injections for the treatment of joints.…”
Section: The Svf: Rise and Riskmentioning
confidence: 99%
“…When compared head to head, however postmenopausal women with hormone receptor positive breast cancer receiving anastrozole displayed significantly fewer incidence of steatosis compared to the tamoxifen arm 14.6% vs 41% at 3 year follow-up P <0.001. 9 …”
Section: Introductionmentioning
confidence: 99%